Using program impact pathways to understand and improve program delivery, utilization, and potential for impact of Helen Keller International's Homestead Food Production Program in Cambodia - Olney, Deanna K.; Vicheka, Sao; Kro, Meng; Chakriya, Chhom; Kroeun, Hou; Hoing, Ly Sok; Talukder, Aminzzaman; Quinn, Victoria; Iannotti, Lora L.; Becker, Elisabeth; Roopnaraine, Terry (SAGE Publications, 2013)
Evidence of the impact of homestead food production programs on nutrition outcomes such as anemia and growth is scant. In the absence of information on program impact pathways, it is difficult to understand why these programs, which have been successful in increasing intake of micronutrient-rich foods, have had such limited documented impact on nutrition outcomes.To conduct a process evaluation of Helen Keller International's (HKI's) homestead food production program in Cambodia to assess whether the program was operating as planned (in terms of design, delivery, and utilization) and to identify ways in which the program might need to be strengthened in order to increase its potential for impact.A program theory framework, which laid out the primary components along the hypothesized program impact pathways, was developed in collaboration with HKI and used to design the research. Semistructured interviews and focus group discussions with program beneficiaries ( n = 36 and 12, respectively), nonbeneficiaries ( n = 12), and program implementers ( n = 17 and 2, respectively) and observations of key program delivery points, including health and nutrition training sessions ( n = 6), village model farms ( n = 6), and household gardens of beneficiaries ( n = 36) and nonbeneficiaries ( n = 12), were conducted to assess the delivery and utilization of the primary program components along the impact pathways.The majority of program components were being delivered and utilized as planned. However, challenges with some of the key components posited to improve outcomes such as anemia and growth were noted. Among these were a gap in the expected pathway from poultry production to increased intake of eggs and poultry meat, and some weaknesses in the delivery of the health and nutrition training sessions and related improvements in knowledge among the village health volunteers and beneficiaries.Although the program has been successful in delivering the majority of the program components as planned and has documented achievements in improving household production and intake of micronutrient-rich foods, it is likely that strengthening delivery and increasing utilization of some program components would increase its potential for nutritional impacts. This research has highlighted the importance of designing a program theory framework and assessing the components that lie along the primary program impact pathways to optimize program service delivery and utilization and, in turn, potential for impact.